ANALISIS PERTUMBUHAN EKONOMI, INVESTASI, DAN KONSUMSI DI INDONESIA - Ernita, Dewi; Amar, Syamsul; Syofyan, Efrizal (Program Studi Magister Ilmu Ekonomi, 2013)
ABSTRACT This study aims to analyze (1) Effect of consumption, investment, government spending, and net exports to economic growth in Indonesia, (2) Effect of interest rates, inflation, and economic growth to investment in Indonesia, (3) Effect of disposable income, consumption previously, and the interest rate on consumption in Indonesia. Data in the form of time series of the first quarter of 2001 to the fourth quarter of 2010. This study using a simultaneous equations model analysis in the form of Two Stage Least Square (2 SLS). The research concludes that (1) consumption, investment, government spending, and net exports have a significant and positive impact on economic growth in Indonesia. If the consumption, investment, government spending, and net exports increased, economic growth will also increase. (2) Interest rates have a significant and negative effect on investment in Indonesia, while inflation is significant and negative effect on investment in Indonesia. If interest rates and inflation down the investment will rise, while economic growth in significant and positive impact on investment in Indonesia. (3) Disposable income and consumption before significant positive impact on consumption in Indonesia. If disposable income and consumption increases, consumer spending earlier will also increase. And interest rates have a significant negative effect on consumption in Indonesia. Keywords : Government Spending, Net Exports, Interest Rates, inflation, Disposable Income, Consumption Previously, Economic Growth, Investment, and Consumption